Endocardial Activation Drives Activation Patterns During Long-Duration Ventricular Fibrillation and Defibrillation. (December 2017) - Panitchob, Nuttanont; Li, Li; Huang, Jian; Ranjan, Ravi; Ideker, Raymond E.; Dosdall, Derek J.
Abstract : Background: Understanding the mechanisms that drive ventricular fibrillation is essential for developing improved defibrillation techniques to terminate ventricular fibrillation (VF). Distinct organization patterns of chaotic, regular, and synchronized activity were previously demonstrated in VF that persisted over 1 to 2 minutes (long-duration VF [LDVF]). We hypothesized that activity on the endocardium may be driving these activation patterns in LDVF and that unsuccessful defibrillation shocks may alter activation patterns. Methods and Results: The study was performed using a 64-electrode basket catheter on the left ventricle endocardium and 54 6-electrode plunge needles inserted into the left ventricles of 6 dogs. VF was induced electrically, and after short-duration VF (10 seconds) and LDVF (7 minutes), shocks of increasing strengths were delivered every 10 seconds until VF was terminated. Endocardial activation patterns were classified as chaotic (varying cycle lengths and nonsynchronous activations), regular (highly repeatable cycle lengths), and synchronized (activation that spreads rapidly over the endocardium with diastolic periods between activations). Conclusions: The results showed that the chaotic pattern was predominant in early VF, but the regular pattern emerges as VF progressed. The synchronized pattern only emerged occasionally during late VF. Failed defibrillation shocks changed chaotic and regular activation patterns to synchronized patterns in LDVF but not in short-duration VF. The regular and synchronized patterns of activation were driven by rapid activations on the endocardial surface that blocked and broke up transmurally, leading to an endocardial to epicardial activation rate gradient as LDVF progressed.